2019
DOI: 10.1111/jcmm.14704
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐590‐3p regulates proliferation, migration and collagen synthesis of cardiac fibroblast by targeting ZEB1

Abstract: Previous studies have implicated the attractive and promising role of miR‐590‐3p to restore the cardiac function following myocardial infarction (MI). However, the molecular mechanisms for how miR‐590‐3p involves in cardiac fibrosis remain largely unexplored. Using human cardiac fibroblasts (HCFs) as the cellular model, luciferase report assay, mutation, EdU assay and transwell migration assay were applied to investigate the biological effects of miR‐590‐3p on the proliferation, differentiation, migration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…However, the role of miR-590-3p in keloid is unclear. A previous study reported that miR-590-3p inhibited cardiac fibroblasts progression [16]. Consistent with this, we also proved the inhibitory effect of miR-590-3p in keloid fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the role of miR-590-3p in keloid is unclear. A previous study reported that miR-590-3p inhibited cardiac fibroblasts progression [16]. Consistent with this, we also proved the inhibitory effect of miR-590-3p in keloid fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, it also can play a tumor-promoting action in colorectal cancer and ovarian cancer [14,15]. Moreover, miR-590-3p represses the progression of cardiac fibroblasts [16].…”
Section: Introductionmentioning
confidence: 99%
“…miR-590-3p could regulate proliferation, migration and collagen synthesis of cardiac fibroblasts by targeting ZEB1. 19 The rapid delivery of miR-590-3p using targeted exosomes can be used as a potential therapeutic phenomenon to treat acute myocardial infarction. 20 miR-590-3p is capable of inducing proliferation of cardiomyocytes and cardiac regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation based on the lncRNA‐mRNA expression correlation network analysis to predict the possible mechanism of these lncRNAs revealed that both NONMMUT032513 and NONMMUT074571 were significantly associated with genes involved in the pathology of MI. For instance, ZEB1, which is positively linked to NONMMUT032513 and NONMMUT074571 in our findings, has been identified as an extremely abundant protein in the infarct area of MI models 43 . The high expression of ZEB1 promotes cardiac fibrosis, stabilizes collagen and aggravates MI by suppressing CXCR4 and increasing the level of collagen cross‐linking enzymes, Col1A1 and Col3A1 44,45 .…”
Section: Discussionmentioning
confidence: 49%
“…For instance, ZEB1, which is positively linked to NONMMUT032513 and NONMMUT074571 in our findings, has been identified as an extremely abundant protein in the infarct area of MI models. 43 The high expression of ZEB1 promotes cardiac fibrosis, stabilizes collagen and aggravates MI by suppressing CXCR4 and increasing the level of collagen cross-linking enzymes, Col1A1 and Col3A1. 44,45 Moreover, the clinical outcome after MI is highly correlated with NF-κB, interleukin (IL)-6…”
Section: Discussionmentioning
confidence: 99%